Status and Culture of Arbuscular Mycorrhizal Fungi isolated from rhizosphere of Endemic and Endangered Species of Kalapi (Kalappia celebica Kosterm) - Asrianti, Arif; Tuheteru, FD; Husna Kandari, AM; Mekuo, Masnun, IS. (European Journal of Sustainable Development, 2016)
Southeast Sulawesi has many local and endemic plants which important to be develop. One of them is kalapi (Kalappia celebica Kosterm) that has high quality of timber. However, kalapi population in nature have reduce and become rare. Irregular flowering period and limited seed are the problem, beside over exploitation that also threaten the existing of this species. Improve the plant growth and plant survival in degraded forest or marginal environmental conditions should be done using introduce biological agents such as arbuscular mycorrhizal fungi (AMF). The use of soil microorganism like AMF has been done for the conservation programs of rare, endemic and endangered species. This study aimed to determine the AMF status and to assess the culture of AMF which isolated from kalapi soil rhizosphere. Soil and root was taken in field, observations of AMF colonization and spores density carried out in the laboratory of Forestry, production of inoculum carried out in screen house Faculty of Forestry and Environmental Science, soil analysis was conducted in soil chemical laboratory, Faculty of Agriculture, Halu Oleo University. Results of study showed that spore density and AMF colonization have decreased with increasing of fertilizers doses application. 10 g sago waste application/pot and 1 ml hyponex red/ pot is the best treatments which resulted the higher spore density and AMF colonization. The three genera of arbuscular mychorrizal fungi were found, namely Glomus, Gigaspora and Acaulospora genera. Glomus was recorded as the dominant species. This study was an initial step to provide AMF inoculums as biofertilizer to enhance growth of kalapi in support kalapi conservation and other endangered plants in the Southeast Sulawesi. AMF inoculums with sago waste are beneficial combination and can be used as biology fertilizer for plants. Key words: Arbuscular mycorrhiza fungi, sago waste, hyponex-red, Kalappia celebica Kosterm